Age and Gender as Determinants of Adult Coping with COVID-19 Pandemic (Global Journal of Science Frontier Research, 2020)
Abstract not found
Keywords: coping; national resilience; community resilience; individual resilience; sense of danger; distress symptoms; wellbeing